MYANIMACH – Aplikasi Mobile Untuk Membantu Binatang Yang Diabaikan - Zaki Izzani Akbar; Siti Julianingsih Nurfitriyani; Calvin Leonardo; Salicca Dewi Rahajeng; Harco Leslie Hendric Spits Warnars (Sekolah Tinggi Teknik - PLN, 2019)
Currently, there is no specific platform to manage the adoption process for stray animals in Indonesia. This paper describes the design of a Mobile Application created to address this issue in Jakarta, named myAnimach. This app allows strays and potential adopters to meet their needs easier. myAnimach provides a user-friendly, generic user interface to help them find the strays that meet their criteria or make a post about strays in their neighborhood. Users who want to adopt or offer animals to be adopted can log in or create an account on myAnimach. If the user is interested in becoming an adopter, they need to fill the adoption form. There are several stages in the adoption process. The completion of all the stages will result in an issuance of an adoption letter from myAnimach. Aside from adopting animals, users can also look for adopters for their animals by filling out the upload form on the mobile application.